2014
DOI: 10.5799/ahinjs.01.2014.03.0427
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 10 cmH 2 O positive end-expiratory pressure on arterial oxygenation, respiratory mechanics and hemodynamic parameters in laparoscopic cholecystectomy operations

Abstract: The effects of 10 cmH 2 O positive end-expiratory pressure on arterial oxygenation, respiratory mechanics and hemodynamic parameters in laparoscopic cholecystectomy operations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This is in line with the results from a study where 10 cm PEEP was found to be optimal in their patients population with lower PaCO2 values in the PEEP group reflecting better gas exchange with PEEP. 13 Hemodynamically, we found that the PEEP group showed statistically lower mean arterial pressure though they did not require any vasopressor support. In our study the patients were of ASA physical status 1 and 2, without any pre existing cardiac morbidity.…”
Section: Discussionmentioning
confidence: 66%
“…This is in line with the results from a study where 10 cm PEEP was found to be optimal in their patients population with lower PaCO2 values in the PEEP group reflecting better gas exchange with PEEP. 13 Hemodynamically, we found that the PEEP group showed statistically lower mean arterial pressure though they did not require any vasopressor support. In our study the patients were of ASA physical status 1 and 2, without any pre existing cardiac morbidity.…”
Section: Discussionmentioning
confidence: 66%